Penerapan Teknologi Untuk Pengawasan Anak Dalam Mrnggunakan Gadget Pada Komunitas Orangtua Di Dusun Putat, Kecamatan Patuk, Gunungkidul - Khasanah, Rahayu; Mawadati, Argaditia; Sulistyaningsih, Eka; Ardiansyah, Firdaus; Sejati, Tomy Farhan (DHARMA BAKTI, 2022)
Nowadays, because of the high technology lifestyle, the gadget is not only used byadults but also children. Continuous use of gadgets for social media, playing games orwatching entertainment for children can have a negative impact, but many parents still donot understand this and let their children play gadgets without supervision. Based on thesurvey in Putat village, Patuk, Gunungkidul, the community service program was carried outto educate parents how to be wise parents in the digital era by introducing the digital nativeworld to parents, as well as educating them to be able to prepare children to face the rapiddevelopment of technology in an effort to build a physically and mentally healthy family.These new skills are in the form of how to communicate with children regarding gadgets,how to make agreements with children and how to protect children's gadgets using thetechnology application in each person’s gadget. The program activities had run smoothlyand with direct practice includes in the activities, it can further motivate the community todirectly apply the shared knowledge. The questionnaire result shows that the communityagree that this program provided provisions to the community in the form of thinking skillsor other skills, and the application/implementation of community service in communitylearning efforts has been able to increase the people's reasoning ability.